2013
DOI: 10.1128/mcb.00136-13
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Influences Cancer Cell Differentiation In Vivo

Abstract: dLimitless reproductive potential is one of the hallmarks of cancer cells. This ability is due to the maintenance of telomeres, erosion of which causes cellular senescence or death. While most cancer cells activate telomerase, a telomere-elongating enzyme, it remains elusive as to why cancer cells often maintain shorter telomeres than the cells in the surrounding normal tissues. Here, we show that forced telomere elongation in cancer cells promotes their differentiation in vivo. We elongated the telomeres of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 34 publications
5
72
0
1
Order By: Relevance
“…Induction of differentiation upon telomerase inhibition by TI-IX occurred within a matter of days, and is therefore not due to critical shortening of telomeres [27,89]. Interestingly, TI-III-mediated telomerase inhibition in hESCs appeared to improve stem-celllike phenotype compared with nontreated hESC controls.…”
Section: Discussionmentioning
confidence: 94%
“…Induction of differentiation upon telomerase inhibition by TI-IX occurred within a matter of days, and is therefore not due to critical shortening of telomeres [27,89]. Interestingly, TI-III-mediated telomerase inhibition in hESCs appeared to improve stem-celllike phenotype compared with nontreated hESC controls.…”
Section: Discussionmentioning
confidence: 94%
“…A different study by Hirashima and colleagues demonstrated that forced elongation of the telomeres in cancer cells promoted their differentiation in vivo . 53 The resulting cells had longer telomeres and were capable of forming tumors in nude mice that surprisingly exhibited many duct-like structures, consistent with adenocarcinoma. We could speculate that long telomere length could potentially contribute to tumor recurrence by regulation of cancer cell differentiation, especially into adenocarcinoma subtype.…”
Section: Discussionmentioning
confidence: 96%
“…These include dysregulation during carcinogenesis in the shelterin proteins [41]. In vitro studies also showed that engineered telomere elongation in prostate cancer cells promoted their differentiation, suggesting selection of cancer cells [42]. However, these alternatives do not contradict the premise that individuals with constitutively long TL are more likely to sustain the 2 nd Hit, which is crucial for carcinogenesis in the two-stage telomere model we propose.…”
Section: The Potential Resolution Of the Cancer-telomere Length Paradoxmentioning
confidence: 93%